Constructivist Career Counseling: A Method for Helping Students Career Decision - Hasby, Andini; Suharso, Puji Lestari (Universitas Islam Negeri Raden Intan Lampung, 2023)
Constructivist career counselling is a form of career counselling that can help students who have difficulty making career decisions due to a lack of information. This research is an intervention program that aims to determine the effectiveness of constructivist career counseling in reducing carestudents' career decision-making difficulties a ququantitativend qualitative research with a single subject ABA design. The research subject was a 21-year-old student, who had difficulty deciding on a career after graduating from college because of the lack of information he had. Measuring the success of counseling was carried out using Career Decision Making Difficulties. The results of the research show that constructivist career counselling can help students overcome career decision making difficulties. Subjects no longer find it difficult to decide on a career and can understand the process of searching for information about careers..